Toward convergence in the St. Petersburg hotel industry through the lens of institutional theory - Päivi Karhunen (Journal for East European Management Studies, 2008)
The article assesses the power of institutional organization theory in explaining enterprise adaptation in post-socialism. Empirical analysis of the hotel sector in St. Petersburg, Russia, shows that industry-level isomorphic forces are not at work during economic transition. Combined with market imperfections, this results in intra-industry strategic diversity. The underlying logic however changes as the transition proceeds. During the transition, diversity is based on local versus foreign management and during the post-transition on the legitimacy of operations. The majority of hotels start operating according to shared norms and practices, whereas the lack of coercive pressures from the state still allows some hotels to operate in the shadow and ignore institutional norms. – – Der Artikel untersucht die Möglichkeiten der institutionellen Organisationstheorie zur Erklärung der Unternehmensanpassung im Post- Sozialismus. Empirische Analysen des Hotelsektors in St. Petersburg, zeigen, dass isomorphe Kräfte auf Industrieniveau während des ökonomischen Überganges nicht funktionieren. Kombiniert mit Marktunvollkommenheiten, führt dies zu intra-industriellen strategischer Vielfalt. Die zugrunde liegende Logik ändert sich jedoch mit fortschreitender Transformation. Während der Transformation basiert die Verschiedenartigkeit auf Gegensätzlichkeit von lokalem zu ausländischem Management, während der Post-Transformation auf der Legitimität der Geschäftstätigkeit. Die Mehrheit der Hotels beginnt, sich an gemeinsamen Normen und Praktiken zu orientieren, wobei der mangelnde Druck von Seiten des Staates noch einige Hotels erlaubt, halblegal zu agieren und institutionelle Normen zu ignorieren.
Keywords: 650; Hotel industry; transition economies; Russia; institutional isonorphism; organizational field